Impact of CAre-related Regret Upon Sleep (ICARUS) cohort study: protocol of a 3-year multicentre, international, prospective cohort study of novice healthcare professionals. Issue 3 (27th March 2018) - Cheval, Boris; Cullati, Stéphane; Pihl-Thingvad, Jesper; Mongin, Denis; Von Arx, Martina; Chopard, Pierre; Courvoisier, Delphine S
Abstract : Introduction: Healthcare professionals are particularly at risk of developing numerous physical and psychological health problems. The experiences of emotional burden associated with providing healthcare, notably care-related regret, have been associated with these health problems, but only using cross-sectional data so far. Evidence of a causal impact of regret has not been assessed. The Impact of CAre-related Regret Upon Sleep (ICARUS) study is the first prospective and international cohort study established to examine how newly practising healthcare professionals adapt to their challenging job by assessing the impact of care-related regret on sleep and job quitting. Method and analysis: The ICARUS cohort study will include newly practising healthcare professionals working in acute care hospitals and clinics recruited between May 2017 and November 2019. Data collection, which will begin as soon as the participant starts working with patients, will consist of a 1-year weekly assessment using a secure web survey. Follow-up data will be collected at 6, 12, 18 and 24 months after the end of the first year. We will collect detailed information on the experience of care-related regret (ie, highest regret intensity, accumulation of regrets and coping strategies related to regrets), sleep problems and job quitting. Moreover, quality of life, health status and burnout will be assessed during the follow-up. Several confounders factors, including sociodemographic characteristics, personality, night shifts and work environment characteristics, will be assessed. Ethics and dissemination: The study was approved by the Ethics Committee of Geneva Canton, Switzerland (CCER2016-02041), the Ethics Committee of London South Bank University (HSCSEP/17/06) and the University Research Ethics Committee of Bedfordshire (UREC106). Other study centres deemed local ethical approval unnecessary since the main ethics committee (Geneva) had already accepted the project. Results will be published in relevant scientific journals and be disseminated in international conferences. Fully anonymised data and questionnaires will be freely accessible to everyone (scientists and general public).